Microstructure and Size Effects on the Mechanics of Two Dimensional, High Aspect Ratio Nanoparticle Assemblies - Marchi, Benjamin C.; Keten, Sinan (Frontiers in Materials, 2019)
Uniaxially arranged nanocomposite structures are common across biological materials. Through efficient structural ordering and hierarchies, these materials exhibit stiffnesses and strengths comparable to the better of their constituents. While much is known regarding the mechanical properties of materials with explicit stiff and compliant phases, substantially less is understood about neat (matrix-free) materials composed from high aspect ratio particles. A promising example of nanoparticle assemblies are cellulose nanocrystal (CNC) thin films, which display desirable elastic and failure properties. Despite the exceptional properties of CNC films, accurately linking their nanoscopic properties to macroscale performance remains a challenge. Therefore, this work assesses the effects of fiber geometry and in-plane topology on the elastic and failure behaviors of neat CNC thin films using an atomistically informed coarse-grained molecular dynamics model. Short fiber films show a greater dependence on their specific in-plane ordering compared to longer fiber films. Furthermore, aligned, brick and mortar type CNC films exhibit a remarkable resiliency to random structural perturbations, particularly for films built from long fibers. Finally, simulation size is shown to affect the apparent failure properties of CNC films, with no meaningful impact on elastic property predictions. The relationships between structure and fiber length, as well as the sensitivities to structural randomness and simulation size, elucidated herein provide a comprehensive overview of the expected mechanics of high aspect ratio nanoparticle assemblies.